チュウソウ タイキ コクサイ キョウドウ カンソク ケイカク (MAP) キカン チュウ ノ ナンキョク ロケット ジッケン ホウコク (1984-1985) - 平澤, 威男; ヒラサワ, タケオ; Hirasawa, Takeo (1989)
P(論文) 中層大気国際共同観測計画(MAP)に対応し, 2年間にわたって昭和基地で実施されたロケットによる中層大気, 電離層大気, オーロラ観測に関しての報告書である。特に, 観測の目的, 計画の立案, 昭和基地ロケット打ち上げ経過, 飛しょう結果, 観測結果などについて報告し, 今後のロケット実験に資することを期した。 During the period of Middle Atmosphere Program (MAP), 11MT-135JA type rockets were launched from Syowa Station, Antarctica, into the middle atmosphere and 5 S-310JA type rockets were launched into the upper atmosphere at various stages of polar substorms. Through the successful rocket flights, we have obtained useful information on the physical processes in the middle and upper atmospheres. The present paper reports the progress of the sounding rocket program at Syowa Station mainly concerning the preparation and transportation of the rockets, the maintenance of the launching facilities, the procedures of the rocket firing and tracking, and the results obtained from the rocket flights. departmental bulletin paper